Violência policial militar em Goiás: sofrimento e resistência - Carvalho, Luiz do Nascimento (2013)
This study examines the issue of military police violence in Goiás (2000-2011), emphasizing the problem of how articulate the experience of losing loved ones in violent actions of police officers and the search for an understanding of such events with appeal Semantic available indirectly victimized by people in situations of murder or disappearance of persons. To analyze these situations, is adopted as the theoretical notion of the Semantic Structure of Consciousness (ESC) of L. S. Vygotsky (1896-1934), inspired by his search for the constitution of a monistic theory of consciousness that relates intellect (cognition) and affection. The analysis focused on the content of three sources: a) newspapers, b) lawsuits filed in the Commission on Human Rights and Participative Legislation Legislative Assembly of the State of Goiás, c) Minutes of the public hearing held in the first half of 2006, in order to discuss the problem of police violence d) documents with records of verbal reports that narrate the events experienced directly or indirectly by the deponents. The results show that from the point of view of the search for understanding of what happened, there is a tendency in testimony to a fatalistic conception that sees the target in the form of law taleão, centered on the notion of debt. Regarding configuration of suffering expressed in the interviews, the notion of debt also appears in the definition of death of an innocent, which, combined with the certainty of impunity when it comes to human justice, produce the deponents different expressions of suffering. These expressions largely linked to the shape of the event, whether murder or "disappearance" as well as the position - active or passive - of respondents in relation to events, resulting in the expression of grief for the loss. The implications for the discussion of the problem of the relationship between consciousness and affection are discussed